Knit mitts : your hand-y guide to knitting mittens & gloves - Atherley, Kate (Interweave, 2017)
Knitting expert, Kate Atherley explains how to measure a hand, assess your yarn selection and gauge, and ultimately customize patterns including the 10 gorgeous ones inside to make the best fitting mitts for you and your loved ones.